Brasilia Rules and Itinerant Justice: «Mobile Dispatch» as a Good Practice in the Judicial District of Lima South - Charaja Coata, María Luisa (2024)
The objective of this article is to know the progress and perspectives of itinerant justice implemented through the «mobile dispatch» program in the judicial district of Lima Sur. The method used is analytical, and as a source, bibliography and statistics on mobile dispatch service have been reviewed. As a result, from the statistics of «mobile dispatch» attention from its implementation in 2019 to 2023; It is reflected that each year the numbers of care for the most vulnerable people have increased, with greater attention in cases of alimony, followed by family violence. It is concluded that mobile dispatch has a positive impact, as a solution to the main problem of barriers to access to justice, poverty, in which the residents of the most populated districts of South Lima find themselves; Therefore, it contributes to guaranteeing human rights and effective access to justice, with equality and nondiscrimination.